Kathleen (Forward) Rorke - Rorke Family (1925)
Cataloguer's title. Kathleen (Forward) Rorke (1894-1979), daughter of Ernest Edward Forward and Tryphena (Butt) Forward, was born at Carbonear on 1 June 1894. She married James Rorke on 23 May 1917 and had three children: Patricia (Rorke) Yorke, James Ernest Rorke and Yvonne (Rorke) Pratt. Kathleen died in 1979. The Rorke Family Photograph Collection contains 301 black and white and 28 colour photographs of the Rorke Family of Carbonear, Newfoundland, as well as the Forward and Bemister families from that area who are linked to it by marriage. Although spanning from the 1840s-1970s, most photos are from 1900-45, showing family events, homes and Newfoundland and Labrador locations. There is also an album of photos taken while James Rorke attended the Leys School in Cambridge, England.